2022
DOI: 10.2196/25597
|View full text |Cite
|
Sign up to set email alerts
|

Acceptability of and Willingness to Take Digital Pills by Patients, the Public, and Health Care Professionals: Qualitative Content Analysis of a Large Online Survey

Abstract: Background Digital pills are pills combined with a sensor, which sends a signal to a patch connected to a smartphone when the pills are ingested. Health care professionals can access patient data from digital pills online via their own interface, thus allowing them to check whether a patient took the drug. Digital pills were developed for the stated goal of improving treatment adherence. The US Food and Drug Administration approved the first digital pills in November 2017, but the manufacturer with… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…However, it is important to note that while our study indicated ethical considerations, contrasting results have been reported in other studies. Some of these studies raised concerns regarding data security, potential dependence on technology, and worrying about the consequence of technological failures (Chevance et al, 2022;Holender et al, 2018) The findings are in line with other studies, which were done in Kenya and South Africa among HIV infected women showing that neutral text message content provides confidentiality, minimize fear and provide self-confidence to women Odeny et al, 2014).…”
Section: Discussionsupporting
confidence: 74%
“…However, it is important to note that while our study indicated ethical considerations, contrasting results have been reported in other studies. Some of these studies raised concerns regarding data security, potential dependence on technology, and worrying about the consequence of technological failures (Chevance et al, 2022;Holender et al, 2018) The findings are in line with other studies, which were done in Kenya and South Africa among HIV infected women showing that neutral text message content provides confidentiality, minimize fear and provide self-confidence to women Odeny et al, 2014).…”
Section: Discussionsupporting
confidence: 74%
“…Digital pills should not be seen as a simple change in how medications are taken, state Chevance et al ( Chevance et al, 2022 ). Instead, they should be seen as a complicated intervention that requires rigorous testing before being extensively employed in everyday clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…Digital drugs raise ethical issues, 6 especially about coercion. Members from disadvantaged communities are more frequently subjected to involuntary and coercive psychiatric treatment.…”
mentioning
confidence: 99%